Gender Equality in the European Union: A Comparative Study of Poland and Germany - Maj, Jolanta, PhD (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
This book describes the transformative power of the European Union in the area of gender equality policy in Poland and Germany from 2004 until 2012. It gives the readers an insight into the process of implementing EU law and the major actors and variables which influence this process and its outcome. The book includes an analysis of national law from the perspective of the implementation of EU directives as well as interviews with experts in this area. It identifies the main actors that support or block the law’s implementation as well as the sociocultural conditioning of the process of implementation and its final outcome in both countries. This shows that every Member State, due to its unique configuration of national actors and conditions, develops a different final way of implementing the same EU law, and therefore the transformative power of the EU leads to divergent outcomes in different Member States.